O controle exercido pelo Tribunal de Contas da União em matéria de contratações públicas e a Lei nº 14.133/2021 - Fernandes, Ana Luiza Queiroz Melo Jacoby (2022)
This dissertation intends to explore the role of the Federal Court of Auditors in the exercise of external control on public procurement in the face of the recently issued Law 14.133/2021 and LINDB, that propose a new approach by the court of auditors in this matter. To this end, studies begin investigating the necessity of control to monitor state activities, as well as the various forms of control put by the Federal Constitution. It is also analyzed how the state apparatus was put by the Constitution to verify the role of external control under the administrative functions of the State. Then there are the main rules that make up the legal regime of control and administrative activity in the field of public procurement to understand how the TCU effectively exercises control over public procurement from the temporal and procedural aspects. We also enter into the parameters of the Court of Auditors' action on the matter in order to effectively verify what are the powers and limitations are for the Court to act on this subject